THE EFFECT OF DIGITAL LITERACY AND HYBRID LEARNING ON STUDENT COMPETENCE IN INDONESIAN SUBJECTS CLASS XI 2021/2022 KALAM KUDUS CHRISTIAN HIGH SCHOOL PEMATANG SIANTAR - Ganovia, Paulus; Efendi, Efendi; Butarbutar, Marisi; Siregar, Robert Tua; Sherly, Sherly (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The phenomenon of digital literacy learning at the Kalam Kudus Christian High School Pematang Siantar is influenced by the learning model used during the pandemic. Hybrid learning system is used in learning has an impact on increasing student competence. The purpose of this research is to find out the description of digital literacy, hybrid learning system and student competence at Indonesian subject in grade XI, and at the same time figuring out the effect of digital literacy and hybrid learning system on student competence. This research was completed with a literature and field research design. The type of data used is qualitative and quantitative data. The data sources used are primary and secondary data. The data was collected through questionnaires, interviews and documentation. The test of instrument through a validity test and reliability test. The technigues of data analysis are the test of descriptive qualitative and quantitative tests. This study stated that digital literacy and hybrid learning system have a positive and significant effect on the competence of students. It was concluded that digital literacy, and hybrid learning system at the competence of student were useful. There was a positive influence, and having a strong relationship in this phenomenon. It is necessary in managing the challenges of the learning data access, improving learning facilities and infrastructure, carrying out supervision and competitions which increasing up the intrest and skills.